Denudation systematics inferred from in situ cosmogenic 10Be concentrations in fine (50–100 µm) and medium (100–250 µm) sediments of the Var River basin, southern French Alps - A. Mariotti; P.-H. Blard; J. Charreau; C. Petit; S. Molliex; S. Molliex; the ASTER Team; the ASTER Team (Earth Surface Dynamics, 2019)
Marine sedimentary archives are well dated and often span several glacial cycles; cosmogenic 10Be concentrations in their detrital quartz grains could thus offer the opportunity to reconstruct a wealth of past denudation rates. However, these archives often comprise sediments much finer (<250 µm) than typically analyzed in 10Be studies, and few studies have measured 10Be concentrations in quartz grains smaller than 100 µm or assessed the impacts of mixing, grain size, and interannual variability on the 10Be concentrations of such fine-grained sediments. Here, we analyzed the in situ cosmogenic 10Be concentrations of quartz grains in the 50–100 and 100–250 µm size fractions of sediments from the Var basin (southern French Alps) to test the reliability of denudation rates derived from 10Be analyses of fine sands. The Var basin has a short transfer zone and highly variable morphology, climate, and geology, and we test the impact of these parameters on the observed 10Be concentrations. Both analyzed size fractions returned similar 10Be concentrations in downstream locations, notably at the Var's outlet, where concentrations ranged from (4.02±0.78)×104<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="91pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="aebcf34e8c69a9594bf1900d9f6c1bce"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="esurf-7-1059-2019-ie00001.svg" width="91pt" height="15pt" src="esurf-7-1059-2019-ie00001.png"/></svg:svg> to (4.40±0.64)×104<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="91pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="b28fe01a0209b602a275e5d0e96f5c22"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="esurf-7-1059-2019-ie00002.svg" width="91pt" height="15pt" src="esurf-7-1059-2019-ie00002.png"/></svg:svg> atoms g−1 of quartz. By comparing expected and observed 10Be concentrations at three major river junctions, we interpret that sediment mixing is efficient throughout the Var basin. We resampled four key locations 1 year later, and despite variable climatic parameters during that period, interannual 10Be concentrations were in agreement within uncertainties, except for one upper subbasin. The 10Be-derived denudation rates of Var subbasins range from 0.10±0.01 to 0.57±0.09 mm yr−1, and spatial variations are primarily controlled by the average subbasin slope. The integrated denudation rate of the entire Var basin is 0.24±0.04 mm yr−1, in agreement with other methods. Our results demonstrate that fine-grained sediments (50–250 µm) may return accurate denudation rates and are thus potentially suitable targets for future 10Be applications, such as studies of paleo-denudation rates using offshore sediments.